Novel and recurrent germline and somatic mutations in a cohort of 67 patients from 48 families with Brooke-Spiegler syndrome including the phenotypic variant of multiple familial trichoepitheliomas and correlation with the histopathologic findings in 379 biopsy specimens - Grossmann, Petr; Vanecek, Tomas; Steiner, Petr; Kacerovska, Denisa; Spagnolo, Dominic V; Cribier, Bernard; Rose, Christian; Vazmitel, Marina; Carlson, J Andrew; Emberger, Michael; Martinek, Petr; Pearce, Robert L; et al. (The American Journal of dermatopathology, 2013)
Brooke-Spiegler syndrome (BSS) is a rare, inherited, autosomal dominant disorder characterized by development of multiple adnexal cutaneous neoplasms including spiradenoma, cylindroma, spiradenocylindroma, and trichoepithelioma. The syndrome of multiple familial trichoepitheliomas (MFT) is considered a phenotypic variant of BSS in which patients present with trichoepitheliomas only. We studied germline and somatic mutations of the CYLD gene by direct sequencing in patients with BSS (n = 49) and MFT (n = 18) using peripheral blood and 90 samples of frozen or formalin-fixed paraffin-embedded tumor tissue selected from 379 available histology specimens. Germline CYLD mutations were found in 51 patients (76%) from 36 families (75%). Germline CYLD mutations were found in 43 of the 49 patients with BSS (88%) but in only 8 of 18 MFT cohort (44%). Twenty-one frameshift, 15 nonsense, 3 missense, and 4 splice site mutations were found in patients with BSS, whereas 1 frameshift, 5 nonsense, and 2 splice site mutations were identified in the MFT cohort. Five novel mutations were identified including 4 frameshift mutations (c.1027dupA/p.T343NfsX7, c.2155dupA/p.M719NfsX5, c.2288_2289delTT/p.F763X, and c.2641delG/p.D881TfsX32) and 1 nonsense mutation (c.2713C>T/p. Q905X). Of the 76 tumors from 32 patients with a germline CYLD mutation, 12 were spiradenomas, 15 spiradenocylindromas, 26 cylindromas, 15 trichoepitheliomas, and 7 were other tumor types. Somatic mutations were detected in 67 specimens of these 76 tumors (88%). Of the 67 somatic mutations, 21 (31%) represented a sequence alteration and 46 (69%) showed loss of heterozygosity. In the remaining 9 cases (12%), the somatic changes remained unknown. A germline CYLD mutation was not detected in 14 tumor samples from 8 patients. In these 14 tumors, somatic mutations were identified in 6 samples (43%), all consisting of sequence alterations (1 sample showed 2 different sequence alterations). In the remaining 8 samples (53%), neither germline nor somatic mutations were found in the lesional tissue. Our study increases the catalog of known CYLD mutations in patients with BSS/MFT to 86 and documents the variability of somatic mutations that may occur in them. We confirm the absence of firm genotype-phenotype correlations and the existence of a subset of patients with BSS/MFT who lack a demonstrable germline CYLD mutation. Further studies are needed to explain the reasons for this phenomenon.
Keywords: ztráta heterozygozity; Biopsy; nádory kůže; Humans; dědičné nádorové syndromy; Skin Neoplasms; Mutation, Missense; lidé středního věku; Frameshift Mutation; mutační analýza DNA; zalévání tkání do parafínu; nádorové supresorové proteiny; Skin; zárodečné mutace; Female; mutace; kůže; dospělí; mladý dospělý; Aged; Phenotype; Loss of Heterozygosity; senioři; lidé; Tumor Suppressor Proteins; posunová mutace; deubikvitinizační enzym CYLD; biopsie; nesmyslný kodon; Adult; DNA Mutational Analysis; Pedigree; missense mutace; rodokmen; ženské pohlaví; Germ-Line Mutation; Codon, Nonsense; Male; Middle Aged; Frozen Sections; fenotyp; Adolescent; genetická predispozice k nemoci; Genetic Predisposition to Disease; Paraffin Embedding; Aged, 80 and over; Young Adult; senioři nad 80 let; Mutation; mužské pohlaví; zmrazené řezy; Deubiquitinating Enzyme CYLD; mladiství; Neoplastic Syndromes, Hereditary